CALCULATION OF TEMPERATURE FIELDS AND QUASISTATIC STRESS-STRAIN STATE OF STIFFENED BY SHELL VISCOELASTIC CYLINDER UNDER UNSTEADY THERMAL LOADING - Senchenkov, I. K.; ChervinkoО. П.; Dolya, E. V. (Computer Science and Applied Mathematics, 2020)
The article is devoted to the numerical simulation of temperature fields and the quasistatic stress-strain state of multilayer cylindrical elements of rocket motor under non-stationary temperature effects. Solid propellant rocket motor (SRM), in particular, is considered. The motor consists of a hollow cylinder propellant, supported on the side surface and the ends of a three-layer shell. The fuel material is assumed to be a linearly viscoelastic material, while the shell is assumed to be a linearly elastic material. The problem of the thermo stress-strain state of the motor with a sharp change of ambient temperature is considered. Equations of viscoelasticity for fuel are simplified by the Shapery method, with volumе deformation assumed to be elastic. In this case, the initial problem is reduced to the problem of thermoelasticity, which is solved by the finite element method using a stepwise integration scheme over time. For the demonstration version of solid propellant rocket motors, the effect of temperature difference on its surface on the deformed state was studied. Estimates are given of tensile deformations on the surface of the channel, as well as radial stresses at the fuel-insulation, insulation-corpus interface when the ambient temperature changes from 20°C to -40°C.